Bibliometric Analysis of the Scientific Production of Costa Rican State Universities Indexed in Scopus, 2011-2019: an Application with the R Language Package "Bibliometrix" - Sáenz León, Silvia (2022)
This article is oriented to the analysis of some bibliometric indicators, applied to the scientific production by the state universities of Costa Rica for the period 2011-2019. Through the R language and the use of the Biblioshiny application from the Bibliometrix library / package, a series of indicators related to productivity by author, affiliation, level of citation, documentary characteristics, scientific consumption, and impact. Among the main findings, it is evident that most of the scientific production of Costa Rica indexed in Scopus comes from state universities, there is a presence of Costa Rican research in all continents not only as participants as leaders or main researchers, but there is also great diversification of publication in journals of multiple disciplines, diversity of research in multiple areas of science and others.